12-Oxophytodienoic Acid Reductase 3 (OPR3) Functions as NADPH-Dependent α, β-Ketoalkene Reductase in Detoxification and Monodehydroascorbate Reductase in Redox Homeostasis. (13th December 2019) - Maynard, Daniel; Kumar, Vijay; Spro, Jens; Dietz, Karl-Josef
Abstract: Arabidopsis ( Arabidopsis thaliana ) 12-oxophytodienoic acid reductase isoform 3 (OPR3) is involved in the synthesis of jasmonic acid (JA) by reducing the α, β-unsaturated double bond of the cyclopentenone moiety in 12-oxophytodienoic acid (12-OPDA). Recent research revealed that JA synthesis is not strictly dependent on the peroxisomal OPR3. The ability of OPR3 to reduce trinitrotoluene suggests that the old yellow enzyme homolog OPR3 has additional functions. Here, we show that OPR3 catalyzes the reduction of a wide spectrum of electrophilic species that share a reactivity toward the major redox buffers glutathione (GSH) and ascorbate (ASC). Furthermore, we show that 12-OPDA reacts with ASC to form an ASC-12-OPDA adduct, but in addition OPR3 has the ability to regenerate ASC from monodehydroascorbate. The presented data characterize OPR3 as a bifunctional enzyme with NADPH-dependent α, β-ketoalkene double-bond reductase and monodehydroascorbate reductase activities (MDHAR). opr3 mutants showed a slightly less-reduced ASC pool in leaves in line with the MDHAR activity of OPR3 in vitro . These functions link redox homeostasis as mediated by ASC and GSH with OPR3 activity and metabolism of reactive electrophilic species.